2022
DOI: 10.3389/fphar.2022.913124
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Anorexia and Pica Behavior in Rats Enhanced by Chronic Stress Pretreatment

Abstract: Background: Chemotherapy-induced nausea and vomiting severely impairs the treatment and prognosis of cancer patients. Depressive mood disorder might aggravate nausea and vomiting in cancer patients; however, the role of neurotransmitters and receptors involved in the mediation of emesis and nausea is still not well elaborated.Methods: The study was carried out based on the chronic unpredictable mild stress–induced depression-like phenotype rat model and cisplatin-induced pica rat model establishment. Forty mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Consistent with our findings, several studies have reported a decrease in normal food intake in rats following cisplatin administration. [20][21][22] When anamorelin was orally administered to rats daily, normal food intake increased in a dose-dependent manner. 16) However, in the present study, anamorelin (30 mg/kg) did not increase food intake, suggesting that the appetite-stimulating effect of anamorelin could not exceed the appetite-suppressing effect of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, several studies have reported a decrease in normal food intake in rats following cisplatin administration. [20][21][22] When anamorelin was orally administered to rats daily, normal food intake increased in a dose-dependent manner. 16) However, in the present study, anamorelin (30 mg/kg) did not increase food intake, suggesting that the appetite-stimulating effect of anamorelin could not exceed the appetite-suppressing effect of cisplatin.…”
Section: Discussionmentioning
confidence: 99%